[Cingerová, N., Dulebová, I., Štefančík, R. 2021. Politická lingvistika. Bratislava: Ekonóm] - Stradiotová, Eva, 1963-
Recenzia na vysokoškolskú učebniceu Politická lingvistika (Nina Cingerová, Irina Dulebová a Radoslav Štefančík).